(untitled) (Takammul : Jurnal Studi Gender dan Islam Serta Perlindungan Anak, 2018)
Healthy personality is a view of personality that is in accordance with the concept of Islamic personality. Individual Muslims are required to have healthy personalities in accordance with Islamic teachings. The reality is still many Muslim individuals have an unhealthy personality in their daily life. This can be seen from the attitude, behavior and mindset of Muslim individuals who are still far from the guidance of Islamic teachings in various aspects of life. If this happens it is feared will affect the generation of Islam. Counseling the development of healthy personality in children can be done based on the phase of child development so that the child is in a state ready to accept and easy to understand what is given. The loving treatment of parents and education on religious values and socio-cultural values is a conducive factor for preparing children for a healthy person. In addition, a harmonious and religious family atmosphere will form a healthy personality in children. Personality owned by children will affect the morals, morals, manners, ethics, and aesthetics of children when interacting and communicating with other people in everyday life wherever he is.